Estudo dos processos de cristalização em fitas magnéticas amorfas - Peixoto, Erilaine Barreto (2015)
In this work, we study the crystallization process in the Fe40Ni40P14B6 and Fe76.5Cu1Nb3Si13.5B6 amorphous magnetic ribbons fabricated by melt spinning technique. The effect of crystallization on the magnetic properties is studied via MvsH data at room temperature carried out to as-cast and heated samples. X-ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetry (TGA), magnetization of the magnetic field (MvsH) and magnetization versus temperature (MvsT) are reported. The values of Curie temperatures determined via TGA measurements are in agreement with that estimated via MvsT data. DSC measurements are carried out in isothermal and non-isothermal modes, and from the non-isothermal results, we define the temperatures of the isotherms. These isothermal data were fitted using the Johnson-Mehl-Avrami (JMA) model to Fe40Ni40P14B6 ribbon yielding an Avrami exponent, m > 2.5, to isothermal curves in the onset of crystallization process and 1.5 < m < 2.5 to intermediate regions of crystallization process. It is worth to comment that we are able to fit the non-isothermal curves for using the JMA model. XRD measurements taken after TGA measurement (T = 800oC) allow us to identify nanoparticles with Fe-Ni-based and Fe3B0.82P0.18 crystallographic phases to Fe40Ni40P14B6 ribbon and nanoparticles with Fe3Si crystallographic phase to the case of Fe76.5Cu1Nb3Si13.5B6 ribbon. The MvsH data are consistent with the crystallization processes which take place in amorphous magnetic materials.